Use of Synonymous Deoptimization to Derive Modified Live Attenuated Strains of Foot and Mouth Disease Virus - Diaz-San Segundo, Fayna; Medina, Gisselle N.; Spinard, Edward; Kloc, Anna; Ramirez-Medina, Elizabeth; Azzinaro, Paul; Mueller, Steffen; Rieder, Elizabeth; de los Santos, Teresa (Frontiers in Microbiology, 2021)
Foot-and-mouth disease (FMD) is one of the most feared viral diseases that can affect livestock. Although the use of inactivated whole antigen vaccine eliminated the disease from most developed nations by the end of last century, recent outbreaks in Europe and Eastern Asia have demonstrated that infection can spread as wildfire causing devastating economic and social consequences. Therefore, it is essential to develop new control strategies that could confer early protection and rapidly stop disease spread. Live attenuated vaccines (LAV) are one of the best choices to obtain a strong early and long-lasting protection against viral diseases. In proof of concept studies, we previously demonstrated that “synonymous codon deoptimization” could be applied to the P1 capsid coding region of the viral genome to derive attenuated FMDV serotype A12 strains. Here, we demonstrate that a similar approach can be extended to the highly conserved non-structural P2 and P3 coding regions providing a backbone for multiple serotype FMDV LAV development. Engineered codon deoptimized P2, P3 or P2 and P3 combined regions were included into the A24Cruzeiro infectious clone optimized for vaccine production, resulting in viable progeny that exhibited different degrees of attenuation in cell culture, in mice and in the natural host (swine). Derived strains were thoroughly characterized in vitro and in vivo. Our work demonstrates that codon deoptimization technologies can be applied to the entire FMDV genome highlighting the potential of this technology to derive novel improved FMD LAV candidates.